Spatial and Temporal Analysis of 2019 Novel Coronavirus (2019-Ncov) Cases in Selangor, Malaysia - Norezuan Abdul Abdul Gani; Nazri Che Dom; Rahmat Dapari; Nopadol Precha (Faculty of Geography, Universitas Gadjah Mada, 2023)
The COVID-19 pandemic continues to wreak devastation on public health systems worldwide, particularly in Selangor, Malaysia, COVID-19 was reported from October 2020 to October 2021 at prevalent rate. In order to control and prevent the spread of this pandemic, which is already underway, there is need to comprehend the spatial dimension of this disease. Therefore, the purpose of this study was to describe the patterns of COVID-19 virus transmission in the state of Selangor. Methods: Using a Geographic Information System (GIS), and the Moran’s Index (MI), spatial distribution of COVID-19 across the entire mukim was mapped and spatial statistical analysis was carried out with indications of local spatial correlations. Results: The finding revealed that the clusters were concentrated in the western and southern regions (Global Moran's I = 0.468, p = 0.05, Z = 7.01) of the state of Selangor, thus, this research provides important information on the regional distribution and temporal dynamics of COVID-19. Conclusion: An assessment of COVID-19's geographic spread can help enhance health care programs and resource allocation in Malaysia, specifically Selangor where the COVID-19 is pandemic.